(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2020)
The study of genetic variation (GV) in 20 Philippine traditional rice varieties (TRVs) were determined in grain morphology such as length (Gl), width (Gwd), and weight (Gwt), grain yield (Gy), and grain micronutrients such as copper (Cu), iron (Fe), manganese (Mn) and zinc (Zn). Analysis of variance obtained highly significant GV among TRVs in all traits. The mean for Gl, Gwd, Gwt, Gy, Cu, Fe, Mn, and Zn contents was 8.56mm, 2.8mm, 20.01g, 2.13t/ha, 8.64ppm, 14.56ppm, 20.79ppm, and 30.26ppm, respectively. The micronutrients in TRVs followed an order as Zn > Mn > Fe > Cu. For the correlation in traits, 11 pairs were significantly correlated; however, only Mn and Zn content in grains was positively and strongly correlated. Other significant pairs were either in positive or negative and moderately correlated. Cluster analysis, on the other hand, revealed five clusters and showed distinct TRV in two clusters. In conclusion, the presence of higher grain micronutrient content in TRVs indicatesa better opportunity for breeders to determine parental genetic resource in breeding rice with high grain micronutrients. Bangladesh J. Sci. Ind. Res.55(1), 35-42, 2020